Eliglustat substrate reduction therapy in children with Gaucher disease type 1 - Ain, Noor Ul; Saith, Armaan; Ruan, Audrey; Yang, Ruhua; Burton, Aaron; Mistry, Pramod K. (Frontiers in Pediatrics, 2025)
ImportanceGaucher disease (GD) is a rare lysosomal storage disorder with limited treatment options for pediatric patients. Oral substrate reduction therapy (SRT) with eliglustat offers a potential alternative, particularly for those with barriers to enzyme replacement therapy (ERT).ObjectiveEvaluate the safety and efficacy of eliglustat SRT in pediatric patients with type 1 Gaucher disease (GD1), both as initial therapy and as a switch from intravenous ERT.DesignA prospective case series was conducted from 2017 to 2024.SettingYale's National Gaucher Disease Treatment Center, New Haven, CT, United States.ParticipantsFourteen pediatric GD1 patients with significant barriers to receiving ERT.InterventionEliglustat SRT was dosed pharmacogenomically based on CYP2D6 metabolizer status.Primary outcomes and measuresPrimary outcomes included safety and efficacy in reversing indicators of disease activity. Secondary outcomes involved changes in patient and parent-reported quality of life, assessed using PROMIS questionnaires.ResultsEliglustat was initiated at a mean age of 12.5 years (range: 6–17 years) and administered for a mean duration of 3.6 years (range: 1–7 years). All patients remained on treatment and exhibited sustained reductions in glucosylsphingosine (GlcSph) levels compared to baseline (p = 0.005). Other disease indicators demonstrated corresponding improvements. Adverse effects were limited to transient gastroesophageal reflux in 3/14 patients (21%). Serial electrocardiograms (EKGs) were normal. Growth and developmental milestones were appropriate for age in all patients. Patients and their parents reported a global improvement in quality of life.ConclusionsEliglustat demonstrated significant clinical benefits in pediatric GD1 patients, as evidenced by reductions in GlcSph levels and other disease indicators. The therapy showed a favorable safety profile comparable to that observed in adults. These findings suggest eliglustat is a promising therapeutic option for pediatric GD1 patients, providing an effective alternative to ERT.